IMPLEMENTASI PENGUATAN PENDIDIKAN MODERASI BERAGAMA DI LINGKUNGAN PENDIDIKAN TINGGI - Abdullah Romdon, Mujib; Berliana, Berliana; Andriawan, Dian (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2023)
The purpose of this study is to find out more about the implementation of strengthening religious moderation policies carried out by the Ministry of Religious Affairs of the Republic of Indonesia, especially in relation to higher education. Today, differences in religion and belief are a major cause of social strife in society. It is important for government organizations to develop innovative programs to address these situations and conditions. The religious moderation program started by the Ministry of Religious Affairs in 2016 is one such initiative that has been put into practice. The research method is a literature study that shows that Indonesia is a multicultural country with a diversity of ethnicities, cultures, and religions. Therefore, it is likely that this diversity will lead to conflicts between various tribes, cultures, and even religions. The results of this study show that an effective approach in fostering inter-religious harmony is to mainstream religious moderation. Religious moderation education policy aims to prevent intolerance, religious fanaticism, and extremism that threaten social stability and national security, as well as encourage harmony between religious communities in Indonesia. Strengthening religious moderation education in learning is effective, using various evaluation techniques, such as group discussions, questionnaires or surveys, assessments and exams, and direct observation. Religious moderation education can help learners understand the place of religion in their lives